Gastrointestinal mucormycosis: Rare presentation and review of literature - Sistla, Radha; Afroz, Tameem; Reddy, Ravishankar; Reddy, Sivananda; Reddy, Sivakumar (Indian Journal of Case Reports, 2020)
Mucormycosis is an emerging life-threatening opportunistic infection. It is commonly seen in immunocompromised patients. Gastrointestinal mucormycosis is rare and only 25% of cases of gastrointestinal mucormycosis are reported antemortem. The stomach is the common site of gastrointestinal mucormycosis. In this study, three cases of gastrointestinal mucormycosis were diagnosed in 1 year. One was a gastric endoscopic biopsy. Two cases were diagnosed in the small intestine, one in the jejunum and one in the ileum. The diagnosis was made on hematoxylin and eosin stains. Gomori Methenamine Silver staining was done to confirm the morphology in all the cases. Mucormycosis shows broad non-septate filamentous hyphae with irregular branching. It is associated with angioinvasion with necrosis and acute inflammation. Cultures were not done as the diagnosis was not suspected.